The value of adenosine deaminase level in assessing activation of inflammatory bowel disease - Gökden, Yasemin; Hot, Semih; Gönen, Can; Kalyon, Semih; Akkan Çetinkaya, Züleyha (Journal of Surgery and Medicine, 2020)
Aim: There is still a need for an ideal laboratory test that can determine the type of disease, the degree of its activity, predict its course, and monitor treatment response in patients with inflammatory bowel disease (IBD). This study aims to investigate the relationship between disease types and activity with Adenosine deaminase (ADA) levels in patients with IBD. Methods: A total of 92 patients with IBD [43 with Crohn’s disease (CD) and 49 with ulcerative colitis (UC)] and 31 healthy control (HC) volunteers were included in this case-control study. Patients’ age, gender, body mass index, location and severity of the disease, medication, endoscopic examination, hemogram, C-reactive Protein (CRP), and ADA results were evaluated. Results: The mean ADA level was 24.87 (9.6 - 74.9) IU/L in the IBD group and 20.8 (13.7 - 38.9) IU/L in the HC group. The difference between the IBD and HC groups was statistically significant (P<0.013), while that between UC and CD groups was not (P=0.76). Mean ADA level was significantly higher in active UC patients than in inactive ones (P<0.001). To distinguish active UC patients from those in remission, a cut-off level of 21.64 U/L was determined for ADA with 77.6% confidence interval, 89% sensitivity and 60% specificity. Mean ADA level was significantly higher in the CD group compared to the HC group. Conclusion: ADA level may be used as an alternative marker to distinguish active UC patients from those in remission, regardless of the disease location and the extent of the affected area.